Dynamic competition between plug-in hybrid and hydrogen fuel cell vehicles for personal transportation - Bento, N. (International Journal of Hydrogen Energy, 2010)
This article addresses the issue of the diffusion of hydrogen cars in the market, particularly the competition with electric cars for the replacement of conventional vehicles. Using the multi-technological competition model developed by Le Bas and Baron-Sylvester's (Diffusion technologique non binaire et schema epidemiologique. Une reconsideration. Economie Appliquee 1995; tome XLVIII(3):71-101), it is shown that the early deployment of plug-in hybrid vehicles-the only electric technology which can compete with fuel cell cars in the multipurpose vehicle field-risks closing the market for hydrogen in the future. Moreover, the advent of the hydrogen vehicle depends on the rapid advancements in fuel cell technologies, as well as on the existence of an infrastructure with a sufficient coverage